PERILAKU JUDI BOLA KAKI ONLINE PADA MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Trinanda, R Ferry A; Tantoro, Swis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research was conducted at the faculty of social sciences and political science university riau, in order to determine the behavior of football gambling online on the student. problems in this study are (1) what the background factors of students playing football gambling online, (2) what is the impact of a football online gambling behaviors in students? The method used in this study is a qualitative research method, as for the sample in this study were students of the faculty of social sciences and political science university riau conducting gambling foot ball online, because the number of students who conduct gambling foot ball online is not known it is in research The writer in taking a sample with snowball sampling technique by determining one or two subjects to be interviewed further on the subject previously received thus further next subject, to collect data researchers using interviews, observation, documentation in analyzing research data. Results of this study can be concluded that the behavior of football gambling online at the social science faculty students and university political science riau in this study is students aged 22-23 years. Subjects in this study amounted to 5 people, consisting of some students directly involved in online gambling games. With the number of informants, researchers are still not able to get a lot of information needed. Populations are identified throughout the Riau University students involved in online gambling games, because the required informants are students who directly know and follow the online gambling game. Based on the results of this study concluded that the behavior of gambling footballs online at students of faculty of social sciences and political science university Riau, which is motivated by economic factors, situational factors, factors desire to try, factors perception of chances of victory, and the factor of the skills and the impact of football gambling online on the university students of social science and political science university riau namely health impact, economic impact, the impact of deviant behavior, academic performance impact, and the impact on personality.Keywords: Behavior, online footbal gambling